Surrogate mother - praiseworthy or stigmatized: a qualitative study on perceptions of surrogacy in Assam, India - Anna Arvidsson; Polly Vauquline; Sara Johnsdotter; Birgitta Essén (Taylor & Francis Group, 2017)
Background: Surrogacy is a reproductive practice that has been strongly marketed in India as a solution for childless couples. As a result, the number of surrogacy clinics is increasing. Meanwhile, a global discourse on surrogacy, originating from a Western perspective, has characterized surrogacy as being exploitative of women in low-income settings, where poverty drives them to become surrogate mothers. Objective: This study explored perspectives on surrogacy from men and women in Assam, an Indian state known to be a low-income setting. Surrogacy arrangements in Assam are still uncommon. It can be expected that the dominant global discourses on surrogacy will be unfamiliar to the general population, and the objective was also to position the results within the divergent global discourses of surrogacy. Methods: In order to explore local views on surrogacy, we conducted individual interviews and focus group discussions with people from various socioeconomic groups in Assam. Results: Our findings reveal that people in Assam perceive surrogacy as a good option for a childless couple, as it would result in a child who is a 'blood' relation - something highly desirable for sociocultural reasons. However, the part played by the surrogate mother complicates local views on surrogacy. Most people consider payment to the surrogate mother contrary to societal norms. A surrogate mother is also often judged in a moral light, either as a 'bad mother' for selling her child, or as a 'noble woman' who has helped a childless couple and deserves payment for her services. Conclusions: In order to decrease the stigmatization of women, a regulatory policy is needed that will take into account the complex understandings of surrogacy and perceptions of surrogate mothers in Indian society. In policy, the possible effect of the dominant exploitation discourse needs to be modulated by local understandings of this reproduction method.